Uji Efektivitas Antibakteri Ekstrak Daun Pisang Mas (Musa Acuminata Colla) terhadap Pertumbuhan Staphylococcus Aureus dan Escherichia Coli - Eka Anjelita Leony; I Gede Angga Adnyana; Sabariah Sabariah; Resna Hermawati (Universitas Malahayati Lampung, 2026)
ABSTRACT Staphylococcus aureus and Escherichia coli are pathogenic bacteria that cause common infectious diseases in humans. Recently, there has been an increase in antibacterial resistance due to inappropriate use. One way to overcome this problem is to look for alternative medicines derived from natural materials, such as the leaves of Musa acuminata colla, which are thought to have antibacterial compounds. This study is a true experimental study with a fully randomized design. The number of experimental units was 24 for one bacteria divided into 6 groups, namely 25%, 50%, 75%, 100% concentration, positive control ciprofloxacin, and negative control distilled water. The results concentrations of 25%, 50%, 75% Musa acuminata colla leaf extract could not inhibit the growth of Staphylococcus aureus. However, at 100% concentration, there is an inhibition zone with an average diameter of 10.62 mm. The results of data analysis using the unpaired T test showed a statistically significant difference between the 100% concentration and the positive control (mean: 33 mm) with a p-value 0.001. Meanwhile, in Escherichia coli there was no zone of inhibition at all test concentrations. The conclusions is Musa acuminata colla leaf extract caused an inhibition zone at 100% concentration, but the antibacterial efficacy needs to be optimized, while for Escherichia coli it had no effect on bacterial growth. Keywords: Musa Acuminata Colla, Staphylococcus Aureus, Escherichia Coli. ABSTRAK Staphylococcus aureus dan Escherichia coli merupakan bakteri patogen penyebab penyakit infeksi yang umum pada manusia. Belakangan ini terjadi peningkatan resistensi antibakteri akibat penggunaan yang tidak tepat. Salah satu cara untuk mengatasi masalah tersebut dengan mencari obat alternatif yang bersumber dari bahan alam contohnya adalah daun Musa acuminata colla yang diduga memiliki senyawa antibakteri. Penelitian ini merupakan true experimental dengan rancangan acak lengkap. Jumlah unit percobaan sebanyak 24 untuk satu bakteri yang dibagi menjadi 6 kelompok yaitu konsentrasi 25%, 50%, 75%, 100%, kontrol positif ciprofloxacin, dan kontrol negatif aquades. Ekstrak daun Musa acuminata colla pada konsentrasi 25%, 50%, 75% tidak menimbulkan zona hambat terhadap Staphylococcus aureus. Namun pada konsentrasi 100%, terdapat zona hambat dengan diameter rerata 10,62 mm. Sedangkan, pada Escherichia coli tidak terdapat zona hambat pada semua konsentrasi uji. Kesimpulannya Ekstrak daun Musa acuminata colla menimbulkan zona hambat pada konsentasi 100%, namun efektivitas antibakteri perlu dioptimasi, sedangkan untuk Escherichia coli tidak berpengaruh terhadap pertumbuhan bakteri. Kata Kunci: Musa Acuminata Colla, Staphylococcus Aureus, Escherichia Coli.